Divergent Sex-Specific Plasticity in Long-Lived Vertebrates with Contrasting Sexual Dimorphism (2014)
ABSTRACT: Sex-specific plasticity can profoundly affect sexual size dimorphism (SSD), but its influence in female larger-SSD vertebrates remains obscure. Theory predicts that sex-specific plasticity may drive SSD evolution if the larger sex benefits from optimal-growth conditions when available (condition-dependent hypothesis), or if attaining a suboptimal size is penalized by selection (adaptive canalization hypothesis). Sex-specific plasticity enhances the size of the larger sex in male-larger-SSD turtles but whether the same occurs in female-larger species is unknown. Sexual shape dimorphism (SShD) is also widespread in nature but is understudied, and whether SShD derives from sex-specific responses to identical selective pressures or from sex-specific selection remains unclear. Here we tested whether sex-specific growth plasticity underlies the development of sexual size and shape dimorphism in the female-larger-SSD turtle, Podocnemis expansa. Individuals hatched from several incubation temperatures and were raised under common-garden conditions with varying temperature and resources. Body size and shape were plastic and sexually dimorphic, but plasticity did not differ between the sexes, opposite to the malelarger turtle Chelydra serpentina. Maternal effects (egg size) were significant on size and shape, suggesting that females increase their fitness by allocating greater energy to enhance offspring growth. Results ruled out the sex-specific plasticity hypotheses in P. expansa, indicating that SSD and SShD do not derive form differential responses to identical drivers but from sex-specific selective pressures. Our results indicate that differential plasticity does not favor males inherently, nor the larger sex, as would be expected if it was a pervasive driver of macroevolutionary patterns of sexual dimorphism across turtle lineages.